Social Media Exposure and Grammar Proficiency of Elementary-Intermediate Students - Jhonmar D. Bergula; Jecell S. Cabriana; Mivelyn R. Denalo; Leziel P. Macapanas; Avery B. Ocop; Alma Sonia Q. Sanchez-Danday; Billy A. Danday (PT FORMOSA CENDEKIA GLOBAL, 2023)
The widespread use of social media has resulted in its popularity as a teaching and learning platform. In this study, the relationship between the intermediate students' social media exposure and their grammar proficiency, particularly their spelling and use of punctuation marks, were determined. A descriptive-correlational design was used by the researchers and quantitative data were collected using modified instruments such as the social media exposure inventory and grammar proficiency test. The participants were 143 students from the 4th, 5th, and 6th grade of an elementary school located in Eastern Visayas, Philippines. Statistical tools such as mean, percentage, standard deviation, eta, and Pearson correlation were used. The researchers found that there is no significant relationship between students' extent of social media exposure and their grammar proficiency. However. It was also found that students’ age has a low positive correlation with their grammar proficiency. Moreover, future studies may focus on the specific platforms used by other grade levels and their impact on grammar competence.